2018
DOI: 10.5815/ijcnis.2018.06.02
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Fuzzy Minimum Spanning Tree based Routing Process through P-Node Fuzzy Multicasting Approach in MANET

Abstract: Abstract-Mobile Ad-hoc Network (MANET) is mostly decentralized and self-adjustable network system. It is significant to optimize the overall network energy utilization and improve packet sending performance by reducing the errors, generated due to different real-life environmental effects. In this paper, considering atmospheric, environmental change and varying distance for topological change, we try to generate the routing cost. By introducing m-minimum (membership value as m) triangular fuzzy number at inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is significant to optimize the overall network energy utilization and improve packet sending performance. By introducing m-minimum (membership value as m) triangular fuzzy number at interval based cost and energy of the network, [16] to handle the atmospheric, environmental change and varying distance for topological change. They generated both fuzzy minimum spanning tree (FMST) for a given n-nodes network and p-node fuzzy multicast minimum spanning tree (pFMMST), in fuzzy interval based format and concluded that, pFMMST is better FMST based packet routing approach.…”
Section: Related Workmentioning
confidence: 99%
“…It is significant to optimize the overall network energy utilization and improve packet sending performance. By introducing m-minimum (membership value as m) triangular fuzzy number at interval based cost and energy of the network, [16] to handle the atmospheric, environmental change and varying distance for topological change. They generated both fuzzy minimum spanning tree (FMST) for a given n-nodes network and p-node fuzzy multicast minimum spanning tree (pFMMST), in fuzzy interval based format and concluded that, pFMMST is better FMST based packet routing approach.…”
Section: Related Workmentioning
confidence: 99%